Synthesis of nitrogen-doped mesoporous carbon spheres with extra-large pores through assembly of diblock copolymer micelles - Tang, J.; Liu, Jian; Li, C.; Li, Y.; Tade, Moses; Dai, S.; Yamauchi, Y. (Wiley-VCH Verlag, 2015)
The synthesis of highly nitrogen-doped mesoporous carbon spheres (NMCS) is reported. The large pores of the NMCS were obtained through self-polymerization of dopamine (DA) and spontaneous co-assembly of diblock copolymer micelles. The resultant narrowly dispersed NMCS possess large mesopores (ca. 16 nm) and small particle sizes (ca. 200 nm). The large pores and small dimensions of the N-heteroatom-doped carbon spheres contribute to the mass transportation by reducing and smoothing the diffusion pathways, leading to high electrocatalytic activity.